Heterostructure enables new deformation mechanisms to enhance strength and work hardening - Bo Gao; Xinxin Dong; Xuefei Chen; Lirong Xiao; Qi Zhou; Xiaodong Han; Dongdi Yin; Hao Zhou; Yuntian Zhu (Materials Research Letters, 2025)
Reflection of geometrically necessary dislocations (GNDs) has been reported effective in increasing strength and ductility of dual-phase alloys. However, this mechanism is rarely observed in conventional single-phase alloys. Here we report the activation of GND reflection by heterostructure in a single-phase steel, which produces high hetero-deformation induced (HDI) stress. Additionally, it promotes the formation of high-density immobile dislocation locks, which, together with HDI stress, produces high strain hardening. It appears that the condition for GND reflection is low stacking fault energy, high strength difference across hetero boundaries. These findings provide further guidance for designing heterostructures to achieve superior strain hardening.